Single modality radical radiotherapy is an acceptable alternative for the older patient with squamous cell carcinoma of the oesophagus - Philip McLoone; Sarah Derby; David McIntosh; Matthew Forshaw; Caroline Lowrie; Derek Grose; Husam Marashi; Christina Wilson (BMJ Open Gastroenterology)
Background Oesophageal cancer remains a common cause of cancer mortality worldwide. Increasingly, oncology centres are treating an older population and comorbidities may preclude multimodality treatment with chemoradiotherapy (CRT). We review outcomes of radical radiotherapy (RT) in an older population treating squamous cell carcinoma (SCC) oesophagus.Methods Patients over 65 years receiving RT for SCC oesophagus between 2013 and 2016 in the West of Scotland were identified. Kaplan-Meier and Cox-regression analysis were used to compare overall survival (OS) between patients treated with radical RT and radical CRT.Results There were 83 patients over 65 years treated with either RT (n=21) or CRT (n=62). There was no significant difference in median OS between CRT versus RT (26.8 months vs 28.5 months, p=0.92). All patients receiving RT completed their treatment whereas 11% of CRT patients did not complete treatment.Conclusion Survival in this non-trial older patient group managed with CRT is comparable to that reported in previous trials. RT shows better than expected outcomes which may reflect developments in RT technique. This review supports RT as an alternative in older patients, unfit for concurrent treatment.